Transport Processes of Seafloor Sediment From the Chukchi Shelf to the Western Arctic Basin. Issue 4 (8th April 2022) - Watanabe, Eiji; Onodera, Jonaotaro; Itoh, Motoyo; Mizobata, Kohei
Abstract: The processes of seafloor sediment transport from the Chukchi shelf to the western Arctic basin were investigated using a pan‐Arctic sea ice‐ocean model and sediment‐trap measurements at four mooring stations: North of Barrow Canyon, North of Hanna Canyon, Northwind Abyssal Plain, and Chukchi Abyssal Plain. The available sediment‐trap data verified that the sinking flux of lithogenic material (LM) originally resuspended from the seafloor for 2010–2020 was simulated reasonably well in the four mooring areas. The model results were analyzed to quantify the spatiotemporal variability of LM and to reveal its background mechanisms. Analysis indicated that the Barrow Canyon throughflow, Chukchi Slope Current (CSC), and mesoscale eddies played important roles in LM redistribution. The CSC controlled the westward transport of LM from the mouth of Barrow Canyon to the Chukchi Borderland. The mesoscale eddies generated north of Barrow Canyon efficiently transported shelf‐origin LM toward the southern Canada Basin. The sinking flux of particulate organic carbon (POC) averaged from September 2010 to August 2020, which was estimated statistically from the simulated LM flux, was 0.13–0.30 gC m −2  yr −1 at 200‐m depth in the southern Canada Basin. This finding reveals that lateral transport of sediment from the Chukchi shelf bottom has a considerable effect on the sinking flux of POC in the western Arctic basin, and suggests that the western Arctic marine biogeochemical cycle is strongly influenced by shelf‐basin exchange that depends on the relative strength of the CSC and mesoscale eddy activity. Plain Language Summary: The Arctic marine ecosystem and carbon cycle are strongly influenced by exchange between the shallow continental shelf and deep basin. We conducted the first attempt to quantify the spatial and temporal variability in transport of seafloor sediment on the decadal scale using numerical model experiments under a realistic framework. The simulation results suggested that the major ocean currents along the Alaskan coast and shelf‐basin boundary are the primary drivers of the horizontal transport of sediment and its subsequent sinking to intermediate layers. Eddies generated near Point Barrow occasionally supply large amounts of shelf‐origin sediment to the interior of the Canada Basin. Although our model experiments did not include biological processes such as phytoplankton growth and zooplankton grazing, the sinking volume of particulate organic carbon (POC) obtained statistically from the simulated sediment transport was consistent with previous observational estimates. This finding indicates that the transport of sediment originating from the shallow shelf bottom accounts for a large part of the sinking POC in the western Arctic basin, and that its variability depends on topographically controlled ocean currents and eddies. Our study will help to understand how marine ecosystem and carbon distribution are changing in the early 21st century. Key Points: We conducted the first modeling attempt to quantify the transport of seafloor sediment in the western Arctic Ocean Barrow Canyon throughflow, Chukchi Slope Current, and mesoscale eddies play important roles in sediment redistribution Sediment transport substantially contributes to carbon supply for the Chukchi Borderland and southern Canada Basin